2021
DOI: 10.15407/spqeo24.03.295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the reagents’ ratio on photoelectric and optical properties of perovskite films for photovoltaics

Abstract: The properties of the synthesized films of organic-inorganic perovskites CH3NH3PbI3 obtained at various ratios of starting reagents (PbI2 and CH3NH3I) have been studied. As a solvent, we used chemically pure dried dimethylformamide (DMF). Organic-inorganic perovskites are promising for photovoltaic applications. It has been shown that regardless of the ratio of the starting reagents, single-phase perovskites are formed, at the same time the microstructure of the films changes significantly. It has been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Non-Si solar cells were also considered, namely with perovskite thin films [21] and CdS/CIGS heterojunctions [22]. In [21], the properties of organic-inorganic cladcrystalline CH3NH3PbI3 thin films synthesized at different ratios of the starting reagents (PbI2 and CH3NH3I) were studied.…”
Section: Energy Randimentioning
confidence: 99%
See 2 more Smart Citations
“…Non-Si solar cells were also considered, namely with perovskite thin films [21] and CdS/CIGS heterojunctions [22]. In [21], the properties of organic-inorganic cladcrystalline CH3NH3PbI3 thin films synthesized at different ratios of the starting reagents (PbI2 and CH3NH3I) were studied.…”
Section: Energy Randimentioning
confidence: 99%
“…Non-Si solar cells were also considered, namely with perovskite thin films [21] and CdS/CIGS heterojunctions [22]. In [21], the properties of organic-inorganic cladcrystalline CH3NH3PbI3 thin films synthesized at different ratios of the starting reagents (PbI2 and CH3NH3I) were studied. The results showed that, regardless of the starting reagents ratio, single-phase crystalline inclusions form and the film microstructure significantly changes.…”
Section: Energy Randimentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the best laboratory samples of elements based on perovskite demonstrate high efficiency and a low cost of their production. However, they have relatively low stability, although some solar cells show stable operation throughout the year [11,12]. This work aims to study the peculiarities of perovskite formation, and structural and electrophysical characteristics of organic-inorganic MAPbI 3 perovskite films depending on the solvent and the ratio of starting reagents.…”
Section: Introductionmentioning
confidence: 99%